Analisa Pengelolaan Air Terjun Curup Maung Sebagai Ikon Wisata Kabupaten Lahat, Sumatera Selatan - Amri Amirrulloh; Selvi Hestriani (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Curup Maung is a waterfall located in Padang Muara Dua, Gumay Ulu, Lahat Regency which is divided by cliff walls and green grasses, this is what makes it look stunningly beautiful and different from most waterfalls. Qualitative research is a new method in which the research process is more concerned with the interpretation of the potential possessed by Curup Maung. The analysis used is the SWOT analysis. Based on the results of research efforts that can be done to develop Curup Maung is optimizing the work system, it takes a tour guide, forming a strong organization and regulation.Keywords: Curup Maung, waterfall, development